Sal‐like protein 4 (SALL4), a stem cell biomarker in liver cancers1. Issue 4 (6th March 2013) - Oikawa, Tsunekazu; Kamiya, Akihide; Zeniya, Mikio; Chikada, Hiromi; Hyuck, Ahn Dong; Yamazaki, Yuji; Wauthier, Eliane; Tajiri, Hisao; Miller, Lance D.; Wang, Xin Wei; Reid, Lola M.; Nakauchi, Hiromitsu
Abstract Liver cancers, including hepatocellular carcinomas (HCCs), cholangiocarcinomas (CCs), and fibrolamellar HCCs (FL‐HCCs) are among the most common cancers worldwide and are associated with a poor prognosis. Investigations of genes important in liver cancers have focused on Sal‐like protein 4 (SALL4), a member of a family of zinc finger transcription factors. It is a regulator of embryogenesis, organogenesis, pluripotency, can elicit reprogramming of somatic cells, and is a marker of stem cells. We found it expressed in normal murine hepatoblasts, normal human hepatic stem cells, hepatoblasts and biliary tree stem cells, but not in mature parenchymal cells of liver or biliary tree. It was strongly expressed in surgical specimens of human HCCs, CCs, a combined hepatocellular and cholangiocarcinoma, a FL‐HCC, and in derivative, transplantable tumor lines in immune‐compromised hosts. Bioinformatics analyses indicated that elevated expression of SALL4 in tumors is associated with poor survival of HCC patients. Experimental manipulation of SALL4′s expression results in changes in proliferation versus differentiation in human HCC cell lines in vitro and in vivo in immune‐compromised hosts. Virus‐mediated gene transfer of SALL4 was used for gain‐ and loss‐of‐function analyses in the cell lines. Significant growth inhibition in vitro and in vivo, accompanied by an increase in differentiation occurred with down‐regulation of SALL4. Overexpression of SALL4 resulted in increased cell proliferation in vitro, correlating with an increase in expression of cytokeratin19 (CK19), epithelial cell adhesion molecules (EpCAM), and adenosine triphosphate (ATP)‐binding cassette‐G2 (ABCG2). Conclusion: SALL4′s expression is an indicator of stem cells, a prognostic marker in liver cancers, correlates with cell and tumor growth, with resistance to 5‐FU, and its suppression results in differentiation and slowed tumor growth. SALL4 is a novel therapeutic target for liver cancers. (HEPATOLOGY 2013)